y
t+1
= −3y
t
+ 4, y
0
= 4
y
t+1
− 0, 2y
t
= 6, y
0
= 4
2y
t+1
− y
t
= 6, y
0
= 7
y
n+1
= 2y
n
− 10, n = 0, 1, . . . , y|
n=0
= y
0
y
n+1
= y
n
, n = 0, 1, . . .
y
t
= 0, 5y
t−1
+ 1, t = 1, 2, . . . , y|
t=1
= y
0
y
t+1
− 0, 1y
t
= 9
y
t
− y
t−1
= −1
y
t+1
− 5y
t
= −2
y
t+1
=
1
3
y
t
+ 6, y
0
= 1
y
t+1
= −
1
4
y
t
+ 5, y
0
= 2
y
t+1
= −2y
t
+ 9, y
0
= 4
y
t+1
− y
t
= 3, y
0
= 5
y
t+1
= b(t) b(t)
+
y
t+1
= a(t)y
t
y
t
= a(0)a(1) . . . a(t − 1)y
0
=
t−1
Y
i=0
a(i)y
0
,
Q
y
t+1
= a(t)y
t
+ b(t)
y
t
=
t−1
Y
i=0
a(i)y
0
+
t−1
X
j=0
b(j)
t−1
Y
i=j+1
a(i).
{y
t
}
t → ∞
y
t+1
=
α
t+1
y
t
; y
t+1
= ay
t
+ t;
y
t+1
= (t + 1)y
t
+ b; y
t+1
= ay
t
+ β
t
;
y
t+1
= α
t
y
t
+ b.